Phenotypic and Comparative Transcriptome Analysis of Different Ploidy Plants in Dendrocalamus latiflorus Munro - Qiao, Guirong; Liu, Mingying; Song, Kunlin; Li, Haiying; Yang, Huiqin; Yin, Yafang; Zhuo, Renying (Frontiers in Plant Science, 2017)
Elucidating the differences in gene expression profiles of plants with different ploidy levels and how they affect phenotypic traits is vital to allow genetic improvement of plants such as Ma bamboo (Dendrocalamus latiflorus Munro). We previously obtained triploid (2n=3X=36), hexaploid (2n=6X=72), and dodecaploid (2n=12X=144) Ma bamboo plants from embryogenic callus by anther culturing. Phenotypic differences between these plants appeared to be correlated with differences in ploidy. Here, we performed transcriptome profiling and sequencing of anther-regenerated plants and F1 seedlings of different ploidy levels using RNA-Seq technology. Pair-wise comparisons of the four resulting libraries revealed 8,396 differentially expressed genes. These differentially expressed genes were annotated, functionally classified, and partially validated. We found that the chromosome doubling led to substantially up- or down-regulation of genes that were involved in cell growth and differentiation; the polyploidy levels altered the anatomical, physiological and growth characteristics, such as leaf thickness, fusoid cell and stomatal size, shoot number, photosynthesis and respiration rate and so on. Additionally, two candidate genes, EXPB3 and TCP with potenitial regulatory roles in cell division and differentiation, were identified through gene coexpresseion network analysis. These results highlight the significance of potential applications of polyploidy, and provide valuable information for the genetic breeding of bamboo species.